Refractive Errors Causing Amblyopia in Children - Qamar Farooq , Maria Waqas , Ali Raza (Journal of Rawalpindi Medical College, 2014)
Background: To categorize the refractive errors of of school children into Myopia, Hypermetropia, Astigmatism and Anisometropia and to determine the rate of Amblyopia in these refractive errors for a more generalized use. Methods: In this cross stectional study visual acuity of eyes of the school children was checked . Those having visual acuity (VA) less than 6/6 in any eye were refracted and the glasses tried. Children unable to read 6/9 or above on Snellens test chart , or having a difference of two or more lines between the two eyes in spite of using prescribed glasses were scheduled for detailed ophthalmic examination to look for the cause of poor vision. Results: A total of 74133 children aging 5-14 years including males and females in equal proportions and comparable ages from 1383 schools were screened by using Snellens chart. 2523 (3.4%) children were found to be subnormal in their vision and 2504(3.378% of total study population) out of them were declared having refractive errors after complete ocular examination.1850 (2.5%) were myopic, 654 (0.88%) hypermetropics and 140 (0.189%) were amblyopics. Of the 140 cases of amblyopia in our study, the cause was anisometropia in 85(60.7%) cases, ametropia in 29 (20.7%) and mixed astigmatism in 26(18/5%) cases.Of the 1850 myopic, 1345(72.7%) were <- 1.0D, 462(25%) were between -1.0D to -4.75D, 43 (2.3%) were -5.0D or more, 120 (6.4%) were having myopic astigmatism ( -1 D) and 61 (3.3%) were amblyopics. In the 654 hypermetropics children the figures were 468 (71.5%), 161 (24.6%), 25 (3.8%), 94 (14.3%), 70 (10.7%) and 79 (12.1%) for hyperopia <+1.0D, +1.0 to +3.75D, +4.0D or more, hyperopic astigmatism , anisometropia and amblyopia, respectively. Of the 61 amblyopia cases in myopia group, anisometropia was present in 34(55.7%) cases, while ametropia and mixed astigmatism were present in 16 (26.2%) and 11 (18,0%) cases of amblyopia. Of the 79 amblyopics in hyperopic group, the relative contribution of anisometropia, ametropia and mixed astigmatism was 51 (64.5%), 13 (16.45%) and 15 (19.0%) respectively. Conclusion: Ambylopia is not uncommon in the early years of life. More hypermetropic children are affected compared to myopic ones. Anisometropia is the most common contributor for ambylopia